INDONESIA'S EFFORTS TOWARD SAUDI ARABIA IN IMPROVING INDONESIAN HAJJ WORSHIP SERVICES IN 2015-2019 - Dika Aditya Putra; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The Hajj is deliberately visiting the Baitullah Al-Haram Kaaba in the city of Mecca, Saudi Arabia, and other historical places and carrying out a series of predetermined worships. In its implementation, various problems occur, ranging from transportation, accommodation, catering and health, so The Central Bureau of Statistics (BPS) and the Ministry of Religion of the Republic of Indonesia conducted a survey of the Indonesian Hajj Pilgrims Satisfaction Index (IKJHI) and the results showed fluctuating numbers in the 2010-2014 period, for this reason the research aimed to find out how Indonesia's efforts towards Saudi Arabia in improving worship services Indonesian pilgrimage 2015 to 2019. The perspective used is Neo-Libralism, with the level of nation-state analysis, and using the theory of foreign policy implementation, as well as with the method of literature study, with a qualitative approach, and the scope of this research is from 2015 to 2019. Indonesia is making efforts towards Saudi Arabia in improving Indonesian Hajj services by carrying out foreign policy by appointing the Indonesian Ambassador to Saudi Arabia as the Hajj coordinator, signing an annual Hajj MoU with Saudi Arabia, and implementing various service innovations such as the e-Hajj system, mandatory Biometrics for pilgrims, 24-hour buses, lottery and accommodation zoning in Mecca, catering with an Indonesian flavor, as well as increasing the role of the Indonesian Ministry of Religion and the Ministry of Hajj and Umrah Affairs of Saudi Arabia as the organizing committee for Hajj. Keywords: Hajj, BPS, survey, IKJHI, fluctuating numbers, effort, Indonesia, Saudi Arabia.